Structural distortions, orbital ordering and physical properties of double perovskite R2CoMnO6 calculated by first-principles. (27th February 2017) - Zhou, Hai Yang; Chen, Xiang Ming
Abstract: The structural distortions, orbital ordering, magnetic and electronic properties of double perovskite R2 CoMnO6 ( R = rare-earth element) have been systematically calculated by first-principles. Structural distortions, including Co–O and Mn–O bond length splitting, the antiferroelectric motions of R ions, the tilting of octahedral (the resulted Co–O–Mn bond angle) are obviously affected by the rare-earth ions' radius. The bond length splitting behavior of Co–O and Mn–O are rather different because of the Jahn–Teller active ion Co 2+ and the Jahn–Teller nonactive ion Mn 4+ . Taking Gd2 CoMnO6 as an example, the t 2g orbitals of Co ions are predicted to be orbital ordered. That is, the spin down channel of d xz orbital for one Co ion and d yz orbital for another Co ion are basically vacant. Finally, the physical properties, including the magnetic Curie temperature and electronic band gap of R2 CoMnO6 are almost linear dependent on the average value of cos 2 θ ( θ is the Co–O–Mn exchange-angle).